Analisis Kesalahan Penggunaan Sufiks -Sa Dan -Mi Pada Pembelajar Bahasa Jepang Tingkat Menengah - Purwansyah, Julistio; Dewanty, Luviana; Haristiani, Nuria (Undiksha Press, 2024)
This study analyzed the misuse of Japanese -sa and -mi suffixes among intermediate learners. The purpose of this research is to describe the suffix usage errors along with their classification and causative factors. The method used in this research is quantitative descriptive method. Based on the analysis, overall errors rate is 46% with -sa suffix usage errors amounting to 29,76% and -mi suffix error usage amounting to 58,33%. The language deviation found classified as errors and mistake, linguistically, the errors classified as morphological and lexical errors, and based on surface strategy the errors classified as misformation. Most of the errors found are intralingual errors caused by overgeneralization, avoidance, ignorance of rule restriction, false concepts hypothesized, and learning strategy. Improving the understanding of both learners and teachers is important to prevent continuous errors. Further research on sakubun making is expected to explore new findings.